Probiotic supplementation for neonates with congenital gastrointestinal surgical conditions: guidelines for future research - Rao, Shripada (2022)
Our pilot RCT found that probiotic supplementation with the three-strain bifidobacterial product (B. breve M-16V, B. longum subsp. infantis M-63 and B. longum subsp. longum BB536) attenuates gut dysbiosis, increases stool short-chain fatty acid (SCFA) levels and improves the growth of head circumference in neonates with congenital gastrointestinal surgical conditions (CGISC). In this article, we have provided guidelines for designing future multicentre RCTs based on the experience gained from our pilot RCT. The recommendations include advice about sample size, potential confounders, outcomes of interest, probiotic strain selection, storage, dose, duration and microbial quality assurance, collection of stool samples, storage and analysis and reporting. Following these guidelines will increase the validity of future RCTs in this area and hence confidence in their results. IMPACT: Probiotic supplementation attenuates gut dysbiosis, increases stool short-chain fatty acid (SCFA) levels and improves the growth of head circumference in neonates with congenital gastrointestinal surgical conditions. The current review provides evidence-based guidelines to conduct adequately powered RCTs in this field.